Gay Star : Belfast Bulletin of the Northern Ireland Gay Rights Association. (Belfast : NIGRA, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: PO Box 44, Belfast BT1 15H
Engels
Periodiek